Biomass Production Assessment in a Protected Area of Dry Tropical forest Ecosystem of India: A Field to Satellite Observation Approach - Thakur, Tarun K.; Patel, Digvesh K.; Thakur, Anita; Kumar, Anirudh; Bijalwan, Arvind; Bhat, Jahangeer A.; Kumar, Amit; Dobriyal, M. J.; Kumar, Munesh; Kumar, Amit (Frontiers in Environmental Science, 2021)
In recent decades, degradation and loss of the world’s forest ecosystems are the key contributors to biodiversity loss and future climate change. This article analyze plant diversity, biomass, carbon sequestration potential (CSP), and net primary productivity (NPP) of four vegetation types viz., Dense mixed forest (DMF); Open mixed forest (OMF); Teak plantation (TP) and Sal mixed forest (SMF) in the dry tropical forest ecosystem of central India through remote sensing techniques together with physical ground observations during 2013-2018. The total C storage in trees varied from 16.02 to 47.15 Mg ha-1 in studied vegetation types with highest in DMF and lowest in OMF. The total C storage in stem wood, branches, and foliage falls in the range of 52.93-78.30%, 9.49-22.99%, and 3.31-12.89% respectively. The total standing biomass varied from 83.77 to 111.21 Mg ha-1, these variations are due to different vegetation types, reflecting highest in DMF followed by TP, SMF while the lowest was estimated in OMF. The net primary productivity (NPP) [aboveground (AG) + belowground (BG)] varied from 7.61 to 9.94 Mg ha-1 yr-1 with mean values of 8.74 Mg ha-1 yr-1 where, AG shares a maximum contribution of 77.66 %. The total biomass production was distributed from 64.09 to 82.91% in AG and 17.08 to 35.91 %, in BG components. The present study narrates that the studied forest ecosystem has substantial potential of carbon sequestration and had great possibility to mitigate local and global climate change.